Konsep Amanah Dalam Al-Qur’an - M. Ihsan Fauzi (STAI Darul Kamal NW Kembang Kerang, 2022)
Abstract - Al-Qur'an is the holy book that was revealed by Allah as a guide to all people. Among the instructions of the Al-Qur'an, there are various, one of which is an invitation to behave with noble morals, such as: honest, fair, gentle, amanah. This paper tries to learn about the concept of amanah in the Al-Qur'an. Regarding the various forms of the word amanah in the Al-Qur'an and their meanings, Al-Qur'an exclamation is known as amanah, and it is also a required attribute for the messenger. The application of the amanah by the objects of the amanah has various scopes, according to their respective responsibilities. Given the importance of applying the amanah in life, we hope that by using this thematic method, we can provide an easier to understand the understanding of the explanation of the amanah verses contained in the Al-Qur'an.